Warehouse Selection for Storage of Finished Goods - Sarinah Sihombing; Gires Firera (Jurnal Manajemen Transportasi & Logistik (JMTRANSLOG), 2014)
In selecting a warehouse for storage of finished goods, from qualitative and quantitative data, aggregate value was obtained as a requirement to make choices and determine costs.